PENGARUH PELATIHAN TERHADAP PENIGKATAN KETERAMPILAN TANI PADA PETANI BAWANG DI DESA TINDALUN KECAMATAN ANGGERAJA KABUPATEN ENREKANG - Zahra Nursyifa; Muh. Ichwan Musa; Uhud Darmawan Natsir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine whether the training has a significant effect on improving the farming skills of onion farmers in Tindalun Village, Enrekang Regency. The population in this study were onion farmers in Tindalun Village, amounting to 60 people. Data collection is done by using the method of questionnaires, observations, and documentation. The data analysis technique used is simple regression analysis using Statistical product and service solution (SPSS). The result of this study indicate that the training has a positive and significant impact on improving the farming skills of onion farmers in Tindalun Village, Anggeraja District, Enrekang Regency.